High performance responsive design building faster sites across devices - Barker, Tom (O'Reilly Media, 2015)
Yes, you can use responsive web design to create high performance, compelling websites. With this practical book, author Tom Barker demonstrates that responsive design is not just a frontend-only approach, but also a philosophy for taking advantage of the entire web stack. Responsive design patterns and anti-patterns, derived from heavily used real-world sites, are guiding principles throughout the book.